2012
DOI: 10.1007/s00262-012-1250-4
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-V promotes anti-tumor immunity and inhibits neuroblastoma growth in vivo

Abstract: The goal of the current study is to determine the effects of blocking phosphatidylserine (PS) on the growth of neuroblastoma in mice. PS, an anionic phospholipid restricted to the cytoplasmic surface of plasma membranes in most cells, is externalized to the surface of apoptotic cells. PS has been shown to induce immune tolerance to self-antigens. PS can also be found on the surface of live cells and in particular tumor cells. Annexin-V (AnV) is a protein that specifically binds and blocks PS. To determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…TNBC represents one of the most malignant subtypes of BC. Current treatment strategies for patients diagnosed with TNBC rely on systemic cytotoxic chemotherapeutics, causing exposure of PS in the tumor microenvironment, which in turn promotes an immunosuppressive condition [ 14 , 52 ]. Previous work has demonstrated that PS-driven immune suppression can be blocked or reversed by PS-targeting antibodies [ 14 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNBC represents one of the most malignant subtypes of BC. Current treatment strategies for patients diagnosed with TNBC rely on systemic cytotoxic chemotherapeutics, causing exposure of PS in the tumor microenvironment, which in turn promotes an immunosuppressive condition [ 14 , 52 ]. Previous work has demonstrated that PS-driven immune suppression can be blocked or reversed by PS-targeting antibodies [ 14 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that exposure of phosphatidylserine in the tumor microenvironment contributes to the immunosuppressed state of tumors (36,43,44). This suggests that the benefit of chemotherapy, radiotherapy, and other treatments that trigger tumor cell apoptosis is undermined by the increase in local tumor immunosuppression caused by phosphatidylserine exposed on dying tumor cells and their microvesicles (25,43,45).…”
Section: Discussionmentioning
confidence: 99%
“…An underlying challenge to virtually all cytotoxic cancer therapies is therapy-induced exposure of PS that exacerbates immunosuppression in the tumor microenvironment (38,49,50). We have found that PS-driven immune suppression can be inhibited by antibody-mediated PS blockade (38,51).…”
Section: Discussionmentioning
confidence: 77%